2009
DOI: 10.1007/s12199-009-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone fracture in physically disabled children attending schools for handicapped children in Japan

Abstract: Objective Very few epidemiologic studies on bone fracture have been conducted in schools for handicapped children (Yogo schools). The aim of this study was to clarify the frequency and risk factors of bone fracture in physically disabled children in Japan. Methods We used a cross-sectional design to examine 525 physically disabled children in 38 Yogo schools in the Hokuriku-Koshinetsu District of Japan. The questionnaire surveyed information on participant sex, age, level of physical disability, and bone fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This finding is close to the rate of 4% found in a systematic review of five studies on children with cerebral palsy[ 3 ] and 3.6% found in schools for physically disabled children, including those with cerebral palsy, traumatic brain injury, encephalitis, myopathy and chromosomal anomalies, in Japan. [ 5 ] In our study, the risk factors for poor bone health included high GMFCS level, lack of regular weight-bearing exercises, being underweight, feeding difficulty, and use of anticonvulsant and steroid. The study also showed that only a minority of children had regular calcium and vitamin D monitoring and supplementation.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is close to the rate of 4% found in a systematic review of five studies on children with cerebral palsy[ 3 ] and 3.6% found in schools for physically disabled children, including those with cerebral palsy, traumatic brain injury, encephalitis, myopathy and chromosomal anomalies, in Japan. [ 5 ] In our study, the risk factors for poor bone health included high GMFCS level, lack of regular weight-bearing exercises, being underweight, feeding difficulty, and use of anticonvulsant and steroid. The study also showed that only a minority of children had regular calcium and vitamin D monitoring and supplementation.…”
Section: Discussionmentioning
confidence: 93%
“…The incidence of fractures with CP is reported at 15–37% 2 , 4 , 7 , 8 ) . Such fractures occur in the lower limb, especially the femurs 9 , 10 ) , and are associated with low BMD 3 ) . Henderson et al.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fragility fracture prevalence varies between 3% and 12% in children in children with predominantly Level V Gross Motor Function Classification (GMFCS; see box 1). [2][3][4] Fractures can recur; the mean age to first fracture was 10 years in one study. 2 These fractures are generally occasioned by lack of a clear history of trauma, as they can occur during normal care activities.…”
Section: Prevalence Of Fractures In Non-ambulant Children With Cpmentioning
confidence: 99%